Prevalence of pathogens from clinical samples associated with porcine respiratory and digestive diseases in South Korea from 2021 to 2023 - Wang, Hye-young; Song, Joong Ki; Shin, Seongho; Kim, Hyunil (Frontiers in Veterinary Science, 2025)
Respiratory and digestive diseases cause significant losses in the swine industry. The current study aimed to investigate the prevalence of viruses and bacteria associated with respiratory/reproductive and digestive diseases in pigs. Clinical samples were collected from 230 farms in South Korea between 2021 and 2023 from pigs with suspected diseases. The pigs were screened for pathogens related to respiratory/reproductive and digestive diseases via multiplex real-time polymerase chain reaction. Of the 104,128 samples, 28,281 [27.2%, 95% confidence interval (CI): 26.9%−27.4%] tested positive for pathogens. The overall prevalence of pathogens related to respiratory/reproductive and digestive diseases was 74.7% (n = 21,145, 95% CI: 74.2%−75.2%) and 25.3% (n = 7,136, 95% CI: 24.7%−25.7%), respectively. Among these pathogens, porcine reproductive and respiratory syndrome virus (PRRSV, n = 11,997, 56.7%, 95% CI: 56.1%−57.4%) and rotavirus (n = 4,430, 62.1%, 95% CI: 60.93%−63.2%) were the most prevalent. The trends in 3-year prevalence showed no significant changes, but in 2023, viral infections (e.g., PRRSV, Rotavirus, porcine epidemic diarrhea virus, etc.) decreased and bacterial infections (e.g., Mycoplasma hyopneumoniae (MH), Pasteurella multocida (PM), Haemophilus parasuis (HP), Salmonella spp., Lawsonia intracellularis, and Brachyspira hyodysenteriae) slightly increased (χ2 = 11.36, P < 0.001). An investigation of seasonal characteristics revealed that the prevalence of some respiratory pathogens such as PRRSV and HP was higher in winter than in other seasons, and the prevalence of digestive bacterial pathogens such as Salmonella spp., L. intracellularis, and B. hyodysenteriae was higher in summer than in other seasons. The study results, including the prevalence of viruses and bacteria, patterns of pathogen frequency, annual distribution status, and seasonal characteristics, are helpful in understanding pathogen trends in porcine respiratory/reproductive and digestive diseases.